Analyzing a group of EFL learners' productsOftwo dictations : Oreseeing orthographical difficulties and planning pronunciation exercises = Análisis del producto de dos dictados por parte de un grupo de estudiantes de inglés: anticipando dificultades ortográficas y planeandoejercicios de pronunciación - Navas Brenes, César Alberto 1976-
This article analyzes the phoneme-grapheme correspondence in the products of two orthographic-text dictations taken by a group of sixteen English majors at the School of Modern Languages at the University of Costa Rica. Accordingly, before administering the dictation of the first text, the author looks for a correlation between a list of foreseen spelling difficulties and the possible mistakes the students will eventually make while decoding and transcribing the troublesome words and phrases of the text. Once the spelling difficulties have been identified, the author presents a series of pronunciation activities to help learners raise awareness towards this spotted difficulty. After this group of students carries out these pronunciation activities, the author administers a second dictation to observe the improvement reached and the effect of formal instruction on the students' second dictation.